Multi-neuromeric origin of tyrosine hydroxylase-positive neurons within the substantia nigra and ventral tegmental area - Ferran, José L.; Lucero-Arteaga, Franco; Ayad, Abdelmalik; Kutsenko, Yevheniy; Alonso, A.; Do-Couto, B. Ribeiro; García-Cabezas, M. Á.; Tseng, Kuei Y. (Frontiers in Neuroanatomy, 2025)
During early developmental stages, the brain is divided into three primary regions: the forebrain (prosencephalon), the hindbrain (rhombencephalon), and the spinal cord. These regions are further segmented into transverse units called neuromeres, each with distinct molecular identities that guide their specialization through development. Such modular organization is evolutionarily conserved and shapes the structural and functional complexity of the brain. The substantia nigra (SN) and ventral tegmental area (VTA) are key midbrain regions involved in reward, motivation, and motor control. They contain dopamine-producing tyrosine hydroxylase (TH)-positive neurons, which are historically classified into three anatomical groups—A8 (retrorubral field), A9 (SN pars compacta), and A10 (VTA)—each with distinct anatomical and functional properties. Recent studies revealed further sub-regional organization along medial-lateral and anterior–posterior gradients, suggesting specialized roles tied to their developmental origins. This study uses the prosomeric framework to map the segmental distribution of TH-positive neurons within the SN and VTA across different mammalian species and developmental stages. Using a comparative analysis of rodent, non-human primate and human specimens, we were able to demonstrate that TH-positive neurons within the SN and VTA exhibit a multi-neuromeric organization, with neuronal populations distributed across the diencephalic prosomeres (dp1-dp3), the midbrain prosomeres (mp1-mp2) and the isthmic rhombomere (r0). It is therefore conceivable that such multi-neuromeric origin of TH-positive neurons within the SN and VTA likely influence the patterns of connectivity and functional specialization of the dopamine system.